THE PANTHEISTIC ONTOLOGY OF NICHOLAS OF CUSA, A FAMOUS REPRESENTATIVE OF RENAISSANCE PHILOSOPHY (Scientific journal of the Fergana State University, 2025)
The article sheds light on pantheistic ideas in the philosophical worldview of the Italian philosopher Nicholas of Cusa. Nicholas of Cusa united the universe with God, inspiring all living things in it, studied nature as a whole, based on the principle of unity, without dividing it into inanimate and animate. All things that appear in the universe, Cusa likens to the threads that a spider weaves from itself, with the help of this metaphor he shows the merging of God with the universe, Cusa understood God not as a person, but as animate nature. The object and subject of knowledge are united in his ontological views, in addition to intellect, Cusa distinguishes intellectual intuition and highly values it. It is through this intellectual intuition that the hidden essence of all things can be known.